2009
DOI: 10.1080/00016340903062836
|View full text |Cite
|
Sign up to set email alerts
|

Influence of highly active antiretroviral treatment (HAART) on risk factors for vertical HIV transmission

Abstract: HAART therapy reduces the influence of the perinatal risk factors on vertical HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Indeed, in France the rate of elective cesarean delivery decreased since 2000 [31]; this has also been reported elsewhere in Europe [26]: The proportion of cesarean delivery in the French perinatal cohort was 52.9% in 2005 through 2010, which was twice the general French cesarean delivery rate [38]. In the same cohort, the proportion of elective cesarean trended from 56% in 2000 to 41% in 2004, whereas that for emergency cesarean section was stable at 29% [23]. In the European Collaborative study, the elective cesarean delivery rate for HIV-infected women declined from 67% in 1999–2001 to 51% by 2005–2007, whereas the emergency cesarean rate ranged from 15 to 17% in the HAART era [24].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, in France the rate of elective cesarean delivery decreased since 2000 [31]; this has also been reported elsewhere in Europe [26]: The proportion of cesarean delivery in the French perinatal cohort was 52.9% in 2005 through 2010, which was twice the general French cesarean delivery rate [38]. In the same cohort, the proportion of elective cesarean trended from 56% in 2000 to 41% in 2004, whereas that for emergency cesarean section was stable at 29% [23]. In the European Collaborative study, the elective cesarean delivery rate for HIV-infected women declined from 67% in 1999–2001 to 51% by 2005–2007, whereas the emergency cesarean rate ranged from 15 to 17% in the HAART era [24].…”
Section: Discussionsupporting
confidence: 53%
“…Most of this increased risk for morbidity is related to infection (e.g., urinary tract infection, pneumonia, wound infection, septicemia), which is elevated for all women undergoing cesarean delivery [20], such that the risks are greatest for cesarean deliveries performed after onset of labor or ruptured membranes, intermediate with scheduled cesarean delivery, and lowest with vaginal delivery [21]. Although the studies upon which existing US guidelines were made demonstrate a clear benefit in reducing MTCT that outweighs potential risks of morbidity, most were conducted before the widespread use of HAART [2123]. As maternal viral load is significantly associated with risk of MTCT [2430], the additional benefit of scheduled cesarean delivery when full viral suppression has been achieved through the use of HAART has been questioned [31–33], and the US guidelines, as mentioned, do not recommend elective cesarean delivery in women with undetectable viral load [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The prescription of HAART to pregnant mothers has demonstrated its effectiveness in the reduction of viral load [15,16], its safety [15] and therefore, a significantly reduced transmission rate of HIV [1,3,15,18]. We observed a significant decrease of maternal viral loads measured at the end of the pregnancy over the study period (figure 2).…”
Section: Discussionmentioning
confidence: 66%
“…The therapeutic strategy to limit MTCT has dramatically changed over time [14][15][16][17][18]. The prescription of HAART to pregnant mothers has demonstrated its effectiveness in the reduction of viral load [15,16], its safety [15] and therefore, a significantly reduced transmission rate of HIV [1,3,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…In group 2, only one baby was HIV positive and CD4 count of the mother was 352/mm 3 compared to 297/mm 3 in women whose babies were HIV negative. Garcia-Tejedor et al 11 reported that CD4 count < 500/mm 3 increased the HIV transmission three times when the mother did not take ART. However, no difference was observed if mother were receiving HAART.…”
Section: Discussionmentioning
confidence: 99%